After‐hours/on‐call experience during primary care nurse practitioner education utilizing standard scenarios and simulated patients. Issue 12 (December 2017) - Kelly, Michelle M.; Blunt, Elizabeth; Nestor, Kelly
Abstract : Background and purpose: : Few nurse practitioner (NP) programs include an after‐hours/on‐call component in their clinical preparation of NP students. This role is expected in many primary and specialty care practices, and is one that students feel unprepared to competently navigate. Methods: : Utilizing simulated callers as patients or parents, NP students participated in a simulated after‐hours/on‐call experience that included receiving the call, managing the patient, and submitting documentation of the encounter. Students completed pre‐ and postparticipation evaluations, and were evaluated by the simulated patient callers and faculty using standardized evaluation tools. Conclusions: : NP students rated the experience as an educationally valuable experience despite feeling anxious and nervous about the experience. Several essential skills were identified including critical thinking, clear communication, self‐confidence, and access to resources. After participation NP students were more receptive to an NP position with an on‐call component. Implications for practice: : Inclusion of a simulated on‐call experience is a feasible component of NP education and should be added to the NP curriculum.